Analisis Perbandingan Kinerja Keuangan Dengan Pendekatan Value for Money dan Rasio Keuangan pada Saat, Sebelum, dan Sesudah Pandemi Covid-19 di Pemerintah Provinsi Jawa Barat - Azhar, Pasya Haikal; Putra, Sugih Sutrisno (Indonesian Accounting Research Journal, 2025)
The Covid-19 pandemic has an impact on the economy which has declined, the Indonesian government has issued a policy to pay attention to financial management by analyzing financial reports. Financial analysis is an analysis of financial reports to determine the financial condition and financial performance of the government. This study aims to compare the financial performance of West Java Province during, before and after the Covid-19 pandemic. This study uses a descriptive quantitative method, analyzing financial performance by measuring Value for Money and financial ratios. The results of the study indicate that the West Java provincial government has been good at managing its finances but has declined during the phase when Covid-19 occurred and is still less than optimal in terms of efficiency because the realization of spending still exceeds the realization of income and dependence which is still categorized as sufficient or there is still dependence due to the existence of special allocation funds for national strategy projects and the lack of BUMD contribution to local revenue because only a few BUMDs contribute to increasing local revenue.